Inside Front Cover Picture: Plasma Process. Polym. 7/2020. Issue 7 (3rd July 2020) - Abessolo Ondo, Dominique; Leturcq, Renaud; Boscher, Nicolas D.
Abstract : Inside Front Cover : Low‐k polymer insulating layers films are produced at atmospheric‐pressure from the nanosecond pulsed plasma reaction of cyclic vinyl organosiloxanes. Variation of the monomer saturation ratio, PM/Psat, impacts the diffusion and adsorption of primary radicals and monomers from the vapour phase to the surface where the polymerisation occurs. Changes in the growth mechanisms affect the dielectric strength and dielectric constant of the formed layers. Further details can be found in the article by Dominique Abessolo Ondo, Renaud Leturcq, Nicolas D. Boscher (e2000032 ).